Transformation of Civil Justice Unity and Diversity (Ius Gentium: Comparative Perspectives on Law and Justice, 2018)
National civil justice systems are deeply rooted in national legal cultures and traditions. However, in the past few decades they have been increasingly influenced by integration processes at the regional, supra-national and international level. As a by-product of the emergence of economic and political unions and globalisation processes there is pressure to harmonise or even unify the way in which national civil justice systems operate. In an attempt to create a 'genuine area of justice', new unified procedures are being developed, which operate in parallel with national civil procedures, and sometimes even strive to replace them. As a reaction to the forces that endeavour to harmonise and unify procedural laws and practices, an opposing trend is gaining momentum: one that insists on diversity and pluralism of national civil procedures. This book focuses on the evolution of procedural reforms in various jurisdictions and the ongoing transformation of national civil justice systems.